Determination Of Criminal Law In The Medical Committee with Artificial Intelligence Supervision Achieves Improvement of the Quality of Doctors at Hospital X in Bekasi City - Dicky Yulius Pangkey; Riswadi , Riswadi (Jurnal Multidisiplin Indonesia, 2025)
Hospitals, as health institutions, are required to continuously improve service quality, including the quality of medical personnel. The Medical Committee serves as an internal body responsible for professional control, including credentialing, performance evaluation, and the enforcement of ethics and discipline. However, challenges in the execution of these roles demand a more objective, accurate, and fast oversight mechanism. Artificial Intelligence (AI) is emerging as a technological solution capable of detecting deviations in medical practice in real time. This research employs a qualitative-retrospective approach at RS X in Bekasi to analyze the implementation of the Medical Committee's duties and the impact of AI-based monitoring on improving doctors' quality. Findings reveal weaknesses in credentialing systems and competency evaluations, as well as incomplete medical documentation that endangers patient safety. The integration of AI proved effective in enhancing professional evaluation systems and reporting. The study recommends implementing AI alongside the reinforcement of criminal law regulations in the medical field to ensure accountability and quality in healthcare services.